2021
DOI: 10.1039/d1fo02077c
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei L9 improves colitis by expanding butyrate-producing bacteria that inhibit the IL-6/STAT3 signaling pathway

Abstract: Inflammatory bowel disease (IBD) is a chronic intestinal inflammation that is currently incurable. Increasing evidences indicate that supplementation with probiotics could improve the symptoms of IBD. It is scientifically significant...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…In contrast to the study above, results of a study showed that Lacticaseibacillus paracasei L9 activated the TLR2/MAPK signaling pathway, promoted the differentiation of DCs to CD103+DCs and CX3CR1+DCs, enhanced the secretion of regulatory cytokines, increased the number of Foxp3+Treg and IL-10+Treg cells, corrected the Th1/Th2 imbalance in the allergic organism, and alleviated the Th1/Th2. The effect of the treatment was to alleviate the symptoms of cow’s milk protein allergy in mice [ 62 ].…”
Section: Probiotics Regulate Immunity Through Intestinal Floramentioning
confidence: 99%
“…In contrast to the study above, results of a study showed that Lacticaseibacillus paracasei L9 activated the TLR2/MAPK signaling pathway, promoted the differentiation of DCs to CD103+DCs and CX3CR1+DCs, enhanced the secretion of regulatory cytokines, increased the number of Foxp3+Treg and IL-10+Treg cells, corrected the Th1/Th2 imbalance in the allergic organism, and alleviated the Th1/Th2. The effect of the treatment was to alleviate the symptoms of cow’s milk protein allergy in mice [ 62 ].…”
Section: Probiotics Regulate Immunity Through Intestinal Floramentioning
confidence: 99%
“…Probiotics are vital components of intestinal microbiota and play an essential role in attenuating inflammatory bowel diseases. Several studies reported that some probiotics could alleviate dextran sulfate sodium (DSS)-induced UC in mice through modulating gut microbiota, such as Lactobacillus rhamnosus [7] and Lactobacillus paracasei [23]. Lacticaseibacillus rhamnosus LS8 (LR), previously isolated from homemade fermented milk, was a potential intestinal microbiota-modulating strain as it can secrete a novel small molecule antibacterial substance-cyclic opine: cycloalanopine (4,6-dimethyl-1,2,5-triazepane-3,7-dione, C6H11N3O2, 157.09 Da, ) and inhibit the growth of food-borne and multidrug-resistant pathogens [24].…”
Section: Introductionmentioning
confidence: 99%
“…16 It was found that L. paracasei L9 ameliorated UC in mice by increasing butyrateproducing bacteria in the intestine, thereby inhibiting the IL-6/ STAT3 signaling pathway. 17 Likewise, another study showed that B. adolescentis ATCC15703 could alleviate experimental UC in mice by modulating the Treg/Th2 response and gut microbiota. 18 Notably, many Lactobacillus and Bif idobacterium strains alleviate UC by acting through their metabolites or structural components, such as exopolysaccharides (EPS), 19 tryptophan metabolites, 20 conjugated linoleic acid, 21 and surface layer proteins (SLP).…”
Section: ■ Introductionmentioning
confidence: 99%